Enhancement of mechanical and tribological properties of Sm-modified Al5083 Alloy through multiaxial forging - G. Aravindh; Preetham Kumar G V; Udaya Bhat K (Results in Engineering, 2025)
The combination of microalloying and severe plastic deformation (SPD) has emerged as a promising strategy for enhancing aluminum alloys' mechanical and tribological properties. This research examines the impact of adding samarium (Sm) to the Al 5083 alloy, followed by multiaxial forging (MAF) at room temperature with a 0.21 strain per pass. The alloy underwent three forging cycles, and its microstructure, mechanical, and tribological properties were assessed using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), universal testing machine (UTM), Vickers microhardness, and reciprocating sliding wear tests. The findings revealed that with each successive forging cycle, the properties of the alloy improved. Following the third cycle, a noticeable reduction in grain size was observed. The highest achieved hardness and tensile strength were 130 ± 3 HV and 380 ± 9 MPa, respectively. Additionally, the wear resistance of the alloy demonstrated significant enhancement, as evidenced by reduced wear volume loss after the third MAF cycle. The specific wear resistance values were 2.2 × 10⁻³, 2.6 × 10⁻³, and 1.3 × 10⁻³ mm³/N-m, while the wear volume loss values were recorded as 12.3 × 10⁻⁷, 26.3 × 10⁻⁷, and 21.9 × 10⁻⁷ µm³ for loads of 1, 2, and 4 N respectively following the third cycle of MAF process.